Widmo ekonomicznej katastrofy czy strach przed komunizmem? Motywy Planu Marshalla w świetle amerykańskich dokumentów - Kowalski, Kamil (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The European Recovery Program was one of the most creative and inspired acts in modern American diplomacy. The article discusses the sequence of events prior to announcement of the Plan at Harvard University within the aim of providing arguments on the significance of economic and political factors of the Marshall Plan. The starting point was set in early 1947 when G. C. Marshall took the office of the Secretary of State. Then the Moscow conference and subsequent radio speech by Marshall is described. The text also comments on D. Acheson’s speech in Delta Council, Cleveland and deals with the Policy Planning Staff established by Marshall soon after his arrival from Moscow conference. The central part of the article is devoted to the report of the Policy Planning Staff (May 1947) and the alarmist memorandum prepared by William Clayton. In the final paragraph, the Marshall Plan speech of June, 5th is analysed in respect of its importance in both economic and political circumstances.
The specter of economic disaster or fear of communism? Themes of the Marshall Plan in the light of american documents
Keywords: Marshall Plan; Cold War; economic reconstruction